2006
DOI: 10.1111/j.1360-0443.2006.01431.x
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of injection drug users’ personal networks and HIV risk behaviors

Abstract: The findings from this study show that, over and above IDUs' baseline characteristics, changes in their personal networks are associated with changes in individuals' risky injection behaviors. They also suggest that interventions aimed at reducing HIV risk among IDUs might benefit from increasing IDUs' social contacts with individuals who are not drug users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 36 publications
5
78
0
1
Order By: Relevance
“…Changes may indicate turnover in and out of the network, or change in the behavior of network members over time. Prior research has suggested that there is a substantial degree of turnover in the present sample (Costenbader et al, 2006). Further exploration with microsocial analysis (Reifman et al, 2006) is indicated.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Changes may indicate turnover in and out of the network, or change in the behavior of network members over time. Prior research has suggested that there is a substantial degree of turnover in the present sample (Costenbader et al, 2006). Further exploration with microsocial analysis (Reifman et al, 2006) is indicated.…”
Section: Discussionmentioning
confidence: 73%
“…A social network consists of an index individual and the individuals with whom the index is connected by interactions or behaviors of interest (Wasserman and Galaskiewicz, 1994). Social networks have been used to examine drug use (e.g., Latkin et al, 1995;Costenbader et al, 2006;Gyarmathy and Neaigus, 2006). Only recently has SNA begun to be used for theory testing (Baerveldt, 2005;Helleringer and Kohler, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There may have been under-reporting of travel due to recall bias, also leading to bias to the null. We also cannot ascribe causality to the associations observed in this study due to its cross-sectional nature, however it is plausible that the circumstances of travel increase the opportunity for risk, for example, by decreasing access to services such as needle exchange, outreach workers, and service providers, and by fluctuations in injecting networks (Costenbader et al, 2006). The associations also might be explained by self-selection, such that persons who engage in high-risk behavior are also more likely to travel.…”
Section: Discussionmentioning
confidence: 86%
“…41 In the analyses, we used both cutoff points to examine whether the associations differed by depression severity.…”
Section: Methodsmentioning
confidence: 99%